Identifying social norms using coordination games: spectators vs. stakeholders - Erkut, Hande; Nosenzo, Daniele; Sefton, Martin (Elsevier, 2015)
We investigate social norms for dictator game giving using a recently proposed norm-elicitation procedure (Krupka and Weber, 2013). We elicit norms separately from dictator, recipient, and disinterested third party respondents and find that elicited norms are stable and insensitive to the role of the respondent. The results support the use of this procedure as a method for measuring social norms.